Modifikasi Tugas dan Lingkungan dalam Pembelajaran Anak Prasekolah dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas - Indah Perjuangan; Fitri Andriani (JIP (Jurnal Intervensi Psikologi), 2009)
Children with attention deficit and hiperactivity have difficulty to concentrate, wich is needed in the learning process. in order to optimalized the process of learning at school and home, researcher modificated the way of learning and environment. Result show that there's increased attention in three weeks of intervention and evaluation. This result could calculated from the increased of attention baseline time in third weeks of attention when learning (1,58 minutes), when make an attention to the material (1,5 minutes), and when doing the material or work of learning (2,9 minutes). Results show, modification in the way of learning and environment have a positive contribution to increase subject's attention of learning process at school and home.Key words: attention, modification in the way of learning and environment